10-minute upcycled projects - Enz, Tammy (North Mankato, Minnesota : Capstone Press a Capstone imprint, 2021)
Looking for clever ideas to reuse and recycle the materials in your makerspace? You're in luck! From earbud bracelets and bottle cap fireflies to tin man wind chimes and cell phone slings, these amazing 10-minute upcycled projects will have kids making in no time!
Got 10 Minutes? -- Earbud Bracelet -- Wearable Washers -- Kitty Lantern -- Firefly Friend -- Crayon Creation -- BFF Puzzle Necklaces -- Tin Man Wind Chime -- T-shirt Pillow -- Poured Paint Luminary -- Pinwheel Collage -- Cell Phone Sleeve -- Snowflake Ornament -- Perfect Painted Planter.
Includes bibliographical references (page 32).
3-6
IG770L
4.7
Keywords: Handicraft -- Juvenile literature; Recycled products -- Juvenile literature; Resourcefulness -- Juvenile literature; Handicraft; Creative ability; Makerspace